Analisis Perbandingan Sifat Mekanik Sambungan Kampuh V Terhadap Kampuh U Hasil Pengelasan SMAW Menggunakan Posisi 3G pada Baja St 37 - Maulana, Rizky; Afdal, Afdal; Abu , Risal; Mukhnizar, Mukhnizar; Selviyanty, Veny (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Selection of the type of support that is appropriate to the load will affect the mechanical and physical properties. Using a good type of support and in accordance with welding procedures can have an influence on the welding results (weldability properties). The comparison of the mechanical properties of V-joints to U-joints is that the maximum tensile stress value between V-joints and U-joints is a maximum of 477.17 N/mm2, while the maximum tensile stress value of V-joints is 453.12 N/mm2. The strain value between the V seam connection and the U seam connection is 20%, while the strain value for the V seam connection is 30%. The yield stress value between the V seam joint and the U seam joint is found in the U seam joint with a yield stress value of 356.05 N/mm2, while the yield stress value for the V seam joint is 337.6 N/mm2. The modulus of elasticity value between the V seam connection and the U seam connection is 2,518.09 N/mm2, while the modulus of elasticity value for the V seam connection is 1,529.43 N/mm2.